Laughter: Feminist Friend or Foe?. Issue 3 (3rd July 2019) - Richmond, Julia C.; Richmond, Kate
Abstract: This is a commentary on Gloria Steinem's (1978 ) essay "If Men Could Menstruate, " which is reprinted in this issue. Here we describe Steinem's work as an example of a comic counterfactual and consider whether this type of humor can advance social justice causes. We discuss the possible impact of feminist humor directed at men in light of current psychological research on men and masculinity and conclude that men may be better able than women to use humor to advance feminism.